PENGELOLAAN REKAM MEDIS DALAM UPAYA PENINGKATAN PELAYANAN PAADA RUMAH SAKIT PERMATA BUNDA MEDAN - mirza febry sanra (Jurnal Pustaka Nusantara dan Budaya, 2013)
This research was conducted at the Permata Bunda General Hospital. The purpose of this study was to determine the management of medical records held at the Permata Bunda General Hospital Medan. This research uses descriptive qualitative method. Characteristics of the informants in this study are the employees who work in the medical record Permata Bunda General Hospital. Data was collected through depth interviews (in-depth interviews), observation, and study documentation. The results showed that the activities of the management of medical records at the Permata Bunda General Hospital performed by the employees did have appropriate procedures. Whether it's government regulated procedures such as government regulations, and procedures manual medical record by the hospital itself. The numbering system is terminal digit medical records filing system, which uses a six-digit number. As for the coding process, the provision of the code referring to the International Classification of Diseases 10 Volume 3. Medical records are stored on open shelves (self open file unit) in consideration of cost, retrieval and retention of medical records more quickly and save space. While the lack of computers and only one employee who has the educational background of medical records can be a problem employee medical records in performing their duties.